Evaluation of factors influencing the maximum crack width of pumice and scoria lightweight concrete one-way slabs - Suseno, Hendro; Soehardjono, Agoes (Engineering and Applied Science Research, 2021)
This paper presents an evaluation of two physical properties of pumice and scoria as coarse aggregates of lightweight concrete, namely high porosity and amorphous glass microstructure that comprises their solid masses. Due to these adverse properties, the tensile strengths of both lightweight concrete materials were low and the bond strengths were also diminished because they have a strong relationship with porosity and microstructure. This study experimentally investigated the influence of low bond strength on the maximum crack width of lightweight concrete one-way slabs using pumice and scoria as coarse aggregates. The tensile strengths were represented by compressive strengths, which are generally considered to be correlated and vary according to the concrete mix proportions. Additionally, the differences of tensile strengths were also evaluated according to the type of coarse aggregate used, i.e., pumice and scoria. Two principal factors influencing the maximum crack width, the ratio of reinforcement and reinforcement tensile stress, were also evaluated for comparison. The lightweight concrete compressive strengths as well as the ratio of reinforcement were varied such that the evaluation could be properly conducted. The results showed that the tensile strength and the type of lightweight coarse aggregate less significantly influenced the maximum crack width. Furthermore, the ratio of reinforcement and the reinforcement tensile stress remained the principal factors influencing the maximum crack width of both types of volcanic lightweight concrete one-way slabs. Hence, these adverse properties should not be taken into account in analysis and design.